Cloud technologies as way to effective professional education - I. L. Lebedeva (Academy of Cognitive and Natural Sciences, 2015)
Research goals: to study the specific application of cloud technologies and realization of their potential for the development of key (core) and special competence of future economists in the use of mathematical methods in modeling of real processes of the economy. Research objectives: to consider the characteristics of the use of cloud technologies in the process of training full-time students; to show the advantages of the combined education in the study of mathematical disciplines of students of economic specialties. Object of research: the teaching process of students of economic specialties. Subject of research: the use of cloud technologies as a means to enhance training effectiveness. Research methods used: theoretical - analysis of scientific and methodical literature; empirical - training, supervision on the educational process, testing of student's competence level. Results of the research. The features of the use of cloudy technologies are considered in the process of professional education of students of full-time teaching. In the context of considerable importance of key jurisdictions there are demonstrated the advantages of the using of the combined education at the study of mathematics by the students of economic specialities. The main conclusions. Information of the learning process and the use of innovative technologies create the conditions for a more rational organization of intellectual activity, thereby increasing the efficiency and quality of training of specialists in all forms of education.